2016
DOI: 10.1007/s00284-016-1165-y
|View full text |Cite
|
Sign up to set email alerts
|

High Perineal and Overall Frequency of Staphylococcus aureus in People Who Inject Drugs, Compared to Non-Injectors

Abstract: To investigate the prevalence, distribution, and colonization burden of Staphylococcus aureus (S. aureus) and MRSA in different body sites among people who inject drugs (PWID) and compare it to a control group consisting of non-injectors. In this cross-sectional survey, 49 active PWID from the needle exchange program (NEP) in Malmö, Sweden, and 60 non-injecting controls from an emergency psychiatric inpatient ward at Malmö Addiction Centre were tested for S. aureus (including MRSA) by culture, PCR, and MALDI-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
8
5
1
Order By: Relevance
“…The prevalence of MRSA nasal carriage (6.79%) in the study is similar to observed studies in other countries [5,[13][14][15]. Notably, the proportion of MRSA in S. aureus isolates were higher than observed studies [5,15].…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of MRSA nasal carriage (6.79%) in the study is similar to observed studies in other countries [5,[13][14][15]. Notably, the proportion of MRSA in S. aureus isolates were higher than observed studies [5,15].…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of MRSA nasal carriage (6.80%) in the study is similar to the afore mentioned studies in other countries [4,[12][13][14]. Notably, the proportion of MRSA in S. aureus isolates were higher than the observed studies [4,14].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, we found that a majority of long-term drug users who took drugs by snorting had few vibrissae. This might also be a potential factor leading to a low prevalence of S. aureus carriage, further studies about the impact of snorting drugs on S. aureus carriage need to be conducted in the future The prevalence of MRSA nasal carriage (6.80%) in the study is similar to the previous studies in other countries [4,[12][13][14], but higher than that in the general population in China [15]. Additionally, the proportion of MRSA in S. aureus isolates was higher than the observed studies [4,14].…”
Section: Discussionsupporting
confidence: 82%